Інститут державно-приватного партнерства в Україні: окремі аспекти - Козар, Ю.; Kozar, Yu.; Гаріфуллін, М. В.; Harifullin, M. V. (Науковий вісник Дніпропетровського державного університету внутрішніх справ. – 2021. – № 4. – С. 173-179, 2021)
Окреслено сучасний стан нормативного та організаційного забезпечення, особливості державно-приватного партнерства в Україні. Акцентовано увагу на активізації планувальної діяльності як закономірному етапі розвитку регіонів і окремих територій та намаганням регіонів знайти адекватні економічні інструменти. Висвітлено роль державно-приватного партнерства у здійсненні економічного та соціально-культурного розвитку об’єднаних територіальних громад. Запропоновано рекомендації щодо шляхів удосконалення розвитку та запровадження стратегічного підходу до планування сталого територіального розвитку.

The article outlines the current state of regulatory and organizational support, features of publicprivate partnership in Ukraine. The emphasis is placed on intensifying planning activities, which on the one hand is a natural stage in the development of regions and individual territories, on the other – the regions’ efforts to find adequate tools to help meet the challenges of todays globalized world, when a variety of changes are accelerating, including political, economic, social, technological, environmental. The topic of public-private partnership in the implementation of economic and socio-cultural development of united territorial communities has been covered. Recommendations on ways to improve development and introduce a strategic approach to sustainable territorial planning have been offered. It has bee noted that the main law in the system of public-private partnership is the Law of Ukraine «On Public-Private Partnership». The definition is given and the features are outlined that depict the relationship of public-private partnership. The definition of public-private partnership as cooperation between the state of Ukraine, the Autonomous Republic of Crimea, territorial communities represented by the relevant state bodies, which in accordance with the Ukrainian law «On management of state property», managing state property, local authorities self-government, the National Academy of Sciences of Ukraine, national branch academies of sciences (state partners) and legal entities, except state and municipal enterprises, institutions, organizations (private partners), carried out on the basis of an agreement in the manner prescribed by the Law «On Public-Private Partnership» and other legislative acts, and meets the characteristics of public-private partnership, defined by this Law. The emphasis is placed on the relevance of strategic planning and development of united territorial communities and focuses on the important role of public-private partnership in the implementation of economic and sociocultural development of territorial communities.

Очерчено современное состояние нормативного и организационного обеспечения, особенности государственно-частного партнерства в Украине. Акцентировано внимание на активизации планировочной деятельности как закономерном этапе развития регионов и отдельных территорий, а так же попыткам регионов найти адекватные экономические инструменты. Освещается роль государственно-частного партнерства в осуществлении экономического и социально-культурного развития объединенных территориальных общин. Предложены рекомендации по путям усовершенствования развития и введение стратегического подхода к планированию устойчивого территориального развития.
Institute of public-private partnership in Ukraine: some aspects
Keywords: державно-приватне партнерство; public-private partnership; государственно-частное партнерство; нормативно-правове регулювання; normative and legal regulation; нормативно-правовое регулирование; соціально-економічний розвиток; socio-economic development; социально-экономическое развитие; об’єднані територіальні громади; united territorial communities; объединенные территориальные общины